DS X-Ray decision support for interpretation of radiographic lesions and clinical management - White, S. C.; Quintessence Publishing Co. (Berlin : Quintessenz Verlag, 2003)
(Producer) Includes more than 250 high-quality and optimized X-ray images accompanied by information on clinical features, diagnostics, differential diagnostics, and therapy of changes that can be shown in X-rays. Can also import your own X-ray images into the program from digital X-ray equipment or data files, making direct comparisons possible
Title from disc label
System requirements: Pentium with at least 233 MHz; 64 MB RAM (128 MB recommended); Windows 98, ME, NT 4.0 (Service Pack 6), 2000, XP; graphics card with 800 x 600 pixel resolution and 24 bit color (true color); CD-ROM drive with 8x read speed; 40 MB free hard disk space
Keywords: Radiography, Dental, Digital; Tooth Diseases -- radiography